A Study of the Electronic Absorption and Emission Spectra of DBDMA Dye: Solvent Effect, Energy Transfer, and Fluorescence Quenching - Al-Hazmy, Sadeq M.; Al-Harby, Jameelah; Hassan, Mohammed; Messaoudi, Sabri; Alhagri, Ibrahim A.; Alhakimi, Ahmed N. (Journal of Spectroscopy, 2023)
This study is aimed to shed light on the electronic absorption and emission spectra of DBDMA (2-(1-(difluoroboraneyl)-1,2-dihydroquinolin-2-yl)-2-(1-methylquinoxalin-2-ylidene) acetonitrile) in different solvents. Both types of spectra were obtained theoretically and produced experimentally in different solvents. The photostability of dye was tested, and its energy transfer behavior in the presence of oxygen and hydrated copper sulfate quenchers was investigated. We also gave a qualitative estimation of the effect of acidic media on the absorption and emission spectra. There is good compatibility between the calculated and measured values of many photophysical parameters. DBDMA has a low chemical quantum yield in solvents of different polarities, and the fluorescence quantum yield is high enough, which confirms, together with the low values of the excited state lifetime, its efficiency as laser emitting dye in the range of wavelength emission maxima. The rigidity of the DBDMA molecule is the main reason for the photochemical stability and the absence of a considerable shift as a result of the change in the polarity of the solvents. Geometries of ground and excited states were optimized using the density functional theory (DFT) and the time-dependent density functional theory (TD-DFT), respectively. Upon using the TD-DFT method, the UV-Vis absorption and emission spectra of the DBDMA molecule in different solvents were illustrated. A slight change is observed in the position of the maximum emission and absorption wavelength with the change of the solvent due to the rigidity of the compound. There was no apparent effect of quenching by oxygen. Besides, no intersystem crossing (ISC) was observed for the excited state of the DBDMA as a result of aeration of a solution with O2 for 20 min, which was an explanation of the stability of peak emission intensity of dye after exposure to oxygen gas. The energy transfer rate constant has been calculated as well.